2019
DOI: 10.3389/fendo.2019.00520
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Activation Prior to Transplantation of Human Ovarian Tissue: Is It Truly Effective?

Abstract: Research Question: What are the true benefits, if any, of disrupting the Hippo signaling pathway and stimulating the Akt pathway in xenotransplanted human ovarian tissue using an in vitro activation (IVA) approach? Design: Human ovarian tissue was retrieved from 18 young patients by laparoscopy and grafted to 54 severe combined immunodeficient mice. The experiment was conducted using fresh ovarian tissue (group I; n = 6 women), sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 48 publications
3
9
0
Order By: Relevance
“…SonerCelik et al [60] research team's findings regarding ovarian cryo-preservation and auto-transplantation demonstrate that expression of inhibitor proteins that control primordial follicle reserve decreases in cryopreserved ovaries after transplantation. The observation is consistent with the ovarian activity rush observed by others [61,62], and thus they debate the recommendation of follicular activation prior (in vitro activation IVA) to transplantation [58,63]. The longevity of the transplanted ovarian tissue varies widely and may depend on the age of the woman at cryo-preservation [64], some blaming the revascularization rate after transplantation as an important issue [65]; however, long functioning viability of more than ten years has been reported [66].…”
Section: New Techniques Of Fertility Preservationsupporting
confidence: 82%
“…SonerCelik et al [60] research team's findings regarding ovarian cryo-preservation and auto-transplantation demonstrate that expression of inhibitor proteins that control primordial follicle reserve decreases in cryopreserved ovaries after transplantation. The observation is consistent with the ovarian activity rush observed by others [61,62], and thus they debate the recommendation of follicular activation prior (in vitro activation IVA) to transplantation [58,63]. The longevity of the transplanted ovarian tissue varies widely and may depend on the age of the woman at cryo-preservation [64], some blaming the revascularization rate after transplantation as an important issue [65]; however, long functioning viability of more than ten years has been reported [66].…”
Section: New Techniques Of Fertility Preservationsupporting
confidence: 82%
“…Moreover, its applicability has been criticized in different aspects. First, it has been associated with a deleterious effect on the ovarian reserve because of a massive and premature follicular activation compromising the development of growing follicles and leading to atresia (‘burn out effect’) ( Grosbois and Demeestere, 2018 ; Dolmans et al , 2019 ). Second, the pathway that becomes activated from this technique has been found altered in several cancers ( Luongo et al , 2019 ), and also showed an increase in DNA damage with a difficult repair when it was applied in bovine follicles culture ( Maidarti et al , 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Even so, histological samples reveal that the pool of follicles will not be completely exhausted until the entry into the eighth decade of life ( Griesinger and Fauser, 2020 ). The main reason for this event is atresia; however, most of them remain in a dormant state caused by certain inactivating factors, while those selected to grow will develop toward the primary stage under control of different signaling pathways ( Dolmans et al , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, secondary follicles collected from frozen-thawed ovaries that were pretreated with collagenase showed normal follicular development. Vitrification of ovaries is known to promote an atretic process in most follicles, except for primordial follicles 19 . However, pretreatment with collagenase prevents atresia and enables the maintenance of developmental competence of secondary follicles.…”
Section: Discussionmentioning
confidence: 99%
“…However, after transplantation the function of frozen-thawed ovarian tissue preserved by vitrification did not improve compared to that of the slowly-frozen ovaries 18 . Furthermore, most follicles, except for primordial follicles, undergo atresia following transplantation or culture 19 .…”
mentioning
confidence: 99%